1988
DOI: 10.1002/polb.1988.090260514
|View full text |Cite
|
Sign up to set email alerts
|

The liquid‐crystalline properties of selected cellulose derivatives

Abstract: The liquid‐crystalline properties of three cellulose esters, phenylacetoxy cellulose (PAC), 4‐methoxyphenylacetoxy cellulose (4MPAC), and p‐tolylacetoxy cellulose (TAC) and two cellulose silyl ethers, trimethyl silyl cellulose (TMSC) and t‐butyldimethylsilyl cellulose (TBDMSC), are reported. Hot‐stage polarized light microscopy provided evidence regarding the formation of thermotropic mesophases in the PAC, 4MPAC, TAC, and TMSC in bulk form upon heating. The concomitant DSC data showed further evidence of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…TMSC was synthesized using the procedures of Pawlowski et al 5,6 from cellulose, DP 202 (Avicel, type PH-105, FMC Corp., Princeton, NJ), and DP 855 (Buckeye Cellulose, Memphis Tenn.). PAC was prepared using the Pawlowski et al procedure from cellulose DP 202, but triethylamine was used in place of pyridine as an acid acceptor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TMSC was synthesized using the procedures of Pawlowski et al 5,6 from cellulose, DP 202 (Avicel, type PH-105, FMC Corp., Princeton, NJ), and DP 855 (Buckeye Cellulose, Memphis Tenn.). PAC was prepared using the Pawlowski et al procedure from cellulose DP 202, but triethylamine was used in place of pyridine as an acid acceptor.…”
Section: Methodsmentioning
confidence: 99%
“…Pawlowski et al 5 synthesized phenyl acetoxy cellulose (PAC), 4-methoxy phenyl acetoxy cellulose, p-tolyl acetoxy cellulose, and TMSC and showed that these materials were thermotropic by using differential scanning calorimetry (DSC) and hot stage microscopy. The substituent groups were readily removed under mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, weak and broad endothermic peaks were detected in the range from 130 to 190°C for the CDA/n-OSAcid ester with DS 0.39 and CDA/i-OSAcid esters with DS 0.15 and 0.22. These broad endothermic peaks may be explained in terms of high molecular mass, polydispersity and the high viscosity of the CDA/OSAcid esters (Pawlowski and Gilbert 1988). Indistinct peaks or baseline shifts were observed for these CDA/ OSAcid esters at 180-190°C, probably due to melting or glass transition points.…”
Section: Relationships Between Reaction Conditions and Ds Of Cda/osacmentioning
confidence: 96%
“…Thus, thermal plasticity can be added to cellulose by b-ketoesterification with OKD molecules having long and branched alkenyl chains. The broadness at the endothermic peak around 170°C for the cellulose/OKD b-ketoester with DS 2.1 may be explained in terms of its high molar mass, polydispersity, high viscosity or low enthalpy of the transition energy (Pawlowski and Gilbert 1988). DSC curves of five cellulose/AKD b-ketoesters are shown in Figure 6.…”
Section: Thermal Properties Of Cellulose B-ketoestersmentioning
confidence: 99%
“…Thermal properties and some unique selfassembling behavior including liquid crystalline properties of cellulose derivatives having long alkyl chains with high DS, i.e. polymer-brush-type cellulose derivatives, have already been reported (Shimamura et al 1981;Isogai et al 1986;Yamagishi et al 1988;Pawlowski and Gilbert 1988;Ito et al 1992;Tsujii et al 1992;Sealey et al 1996;Takada et al 1994Takada et al , 1995Carsten 1996;Hou et al 2000;Cowie et al 2001;Zhou et al 2001;Teramoto and Nishio 2004). Because cellulose b-ketoesters have two long alkyl or alkenyl chains in one substituent, differing from the conventional cellulose ethers or esters having long alkyl chains, some unique thermal properties are expected to appear under particular conditions.…”
Section: Introductionmentioning
confidence: 96%